Recursos hídricos y uso agrícola. Geolocalización de los recursos hídricos en el cantón Latacunga - provincia de Cotopaxi 2015. - Carrera Molina, David Santiago (2016)
With the completion of this research is to demonstrate the importance of studying watersheds and their relationship with agricultural irrigation, as well as providing important to properly manage the most vital human resource tool. Digital terrain models, MDT (Aster Gdem) and GPS was used and observation techniques, data logging, measurement, analysis and calculation documentary was applied. The study area is located in the province of Cotopaxi Latacunga Canton located at latitude 0 ° 56'00 "S Longitude 78 ° 37'00" O Among the results the surface of the upper, middle and lower basin was determined. The surface for the upper basin is 1105.87 has corresponding to 0.8%. raster calculator available in ARC GIS program and the use of a TIN area would be achieved flooding in the main basin of Latacunga Canton was calculated was used to calculate the length of the main river. This surface is 3,195,956.26 m3, corresponding to 77% of the total watershed management in the canton Latacunga is located, taking into consideration that the monthly precipitation to acquire the volume of the said basin is 11541 mm, with a net effectiveness in the reservoir of 0.19%